Film thickness build-up in zero entrainment velocity wide point contacts. (January 2020) - Meziane, Bilel; Vergne, Philippe; Devaux, Nicolas; Lafarge, Lionel; Morales-Espejel, Guillermo E.; Fillot, Nicolas
Abstract: In this work, elastohydrodynamic wide point contacts are studied under Zero Entrainment Velocity (ZEV) conditions. Contrary to classical rolling-sliding contacts, no hydrodynamic lift (oil wedge effect) is expected in stationary isothermal ZEV contacts. However, both experiments and numerical simulations taking into account temperature gradients in the thickness of the lubricant show the occurrence of a full-film lubrication regime over a large range of surface velocities, contact loads and external temperatures. Numerical simulations, including thermal effects but neither transient nor wall slip effects, are in good agreement with experimental film thickness measurements. They allow for both a qualitative description of the mechanisms at stake and to a first tentative minimum film thickness prediction under those specific conditions. Highlights: Numerical simulations of thermoelastohydrodynamic wide point contact under zero entrainement velocity (ZEV). Experimental measurement of film thickness of wide point contact under ZEV. Good experimental and numerical accordance, as a basis to build semi-analytical prediction of film thickness under ZEV. Effects of operating conditions (velocity, load, external temperature) on central and minimal film thickness.